Attitude scale for the dietary therapy of hemodialysis patients: Turkish validity and reliability study ( vol 55 , pg 769 , 2023) - Turan, Guelcan Bahcecioglu; Karabulutlu, Elanur Yilmaz; Ozer, Zulfunaz (Springer, 2025)
[Abstract Not Available]